The lead acceptor in p-type natural 2H-polytype MoS2 crystals evidenced by electron paramagnetic resonance. (12th January 2017) - Iacovo, S; Stesmans, A; Houssa, M; Afanas'ev, V V
Abstract: A low-temperature ( T = 1.5–8 K) electron paramagnetic resonance study of p-type 2H-polytype natural MoS2 crystals reveals a previously unreported anisotropic signal of corresponding defect density (spin S = ½) 5 × 10 14 cm −3 . For the applied magnetic fieldB // c -axis, the response is comprised of a single central asymmetric Zeeman peak at zero-crossing g = 2.102(1), amid a symmetrically positioned hyperfine doublet of splitting 6.6(2) G. Field angular observations reveal a two-branch g pattern, indicative of a defect of lower than axial symmetry, likely orthorhombic ( C 2v ). Based on the signal specifics, it is ascribed to a system of decoupled Pb impurities substituting for Mo, the defect operating as an acceptor, with estimated thermal activation energy >10 meV. Supporting theoretical anticipation, the results pinpoint the conduct of the Pb impurity in layered MoS2 .